Mitigation of annular pressure buildup for deepwater wells using a recovery relief method. Issue 5 (21st June 2019) - Ma, Tianshou; Tang, Yijia; Chen, Ping; He, Yufa
Abstract: Annular pressure buildup (APB) is induced by high‐temperature tubing fluid heating the trapped annular fluid, which leads to liquid thermal expansion at the production stage in deepwater wells. Casing would be burst or collapsed without APB mitigation. A novel recovery relief method was adopted to mitigate APB through the principle of differential pressure. To assess the application effect of the method, APB prediction model and pressure relief threshold determination method were proposed, where the transient heat transfer and volume and pressure coupling were involved. The laboratory test of the principle prototype was conducted so that the feasibility of the recovery relief method was validated. The numerical APB mitigation effect was simulated by the field example. The production simulation results indicated that the high‐temperature‐induced APB caused casing failure. The simulation of APB mitigation with both inward and outward directions demonstrated that the casings using outward mitigation method were safer with lower safe factor. Besides, comparing the mitigating effect to the rupture disk, the recovery relief method had more maximum allowable APB of annulus A. Additionally, compared to other 11 ordinary mitigation methods with the qualities of engineering reliability, technology feasibility, and economy, the recovery relief method had best mitigation performance. Therefore, the recovery relief method was recommended for APB mitigating practice. Abstract : The paper proposed a recovery relief method for annular pressure buildup (APB) mitigation in deepwater wells. The tool is worked by the pressure difference between the adjacent annulus. Both the simulation results and tests validate the feasibility of the method. Also, the tool is compared with other mitigation method, which is found the best overall performance for reliability, feasibility, and economy. Therefore, the recovery relief method is recommended for APB mitigation practice.